2013 Ieee Ro-Man 2013
DOI: 10.1109/roman.2013.6628554
|View full text |Cite
|
Sign up to set email alerts
|

Increasing efficiency in robot-supported assemblies through predictive mechanisms: An experimental evaluation

Abstract: The presented work focuses on investigating the influence of different hand-over timing strategies on the fluency and efficiency of a human-robot team in an assembly task.To this aim, four different timing strategies were experimentally evaluated: (I) a fixed time interval between two handovers, (II) a reactive behavior, where the robot is triggered by the human, (III) fixed time intervals depending on the current component, and (IV) a predictive assembly duration estimation algorithm. During the experiment, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A Bayesian framework is used in [23] to track a human hand position in the workspace with the aim of predicting an action's time-to-completion. The hand must be clearly visible for the estimate to be accurate, which limits certain motions with the aim of obtaining information about time-related aspects of the cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…A Bayesian framework is used in [23] to track a human hand position in the workspace with the aim of predicting an action's time-to-completion. The hand must be clearly visible for the estimate to be accurate, which limits certain motions with the aim of obtaining information about time-related aspects of the cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the sociocognitive aspect, Endsley suggested that efficient collaboration requires common understanding of the task context between humans and robots and common expectations regarding the next step [27]. When two human working partners collaborate on an assembly task, they must be able to estimate the time required by their partner in the assembly process, including the effects of potential external and intrinsic factors (e.g., skill level, fatigue, and stress) that can affect the assembly rate [24]. Aleotti et al suggested that the precise and proactive estimation of handover time points by robots when handing over assembly parts to humans can minimize waiting times and maximize efficiency [28].…”
Section: Handover Tasksmentioning
confidence: 99%
“…In this case, assembly time variation is simply caused by nonattributable random errors (e.g., accidentally dropping an assembly part, sudden itch as a trigger to scratch a body part, etc.). The present study used the common building blocks assembly task [24,25] as a collaborative task between robots and operators to explore the following two work scenarios: (1) a general repetitive assembly task during which mainly only nonattributable random errors occur in the cycle time; and (2) repetitive assembly in which the human operator exhibits a learning curve, resulting in causable and trending cycle time variation. The method-time measurement (MTM), Kalman filter [26], and trigger sensor predictive models were employed to compare the cycle time of the assembly task, waiting times of robot and operator, and the participants' subjective preferences.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of transferring anticipatory action to a human-robot context is also shown in [47], where a significant improvement of task efficiency compared to reactive behavior was possible. For an extensive evaluation of these hypothesis, we want to refer to previous publications [1], [48], [49], [50].…”
Section: Psychological Aspectsmentioning
confidence: 99%
“…In [49] we have presented investigation on the influence of different hand-over timing strategies on the fluency and efficiency of such a human-robot team. Four different timing strategies were experimentally per-formed with 37 volunteers: (I) a fixed time interval between two hand overs, (II) a reactive behavior, where the robot is triggered by the human, (III) a fixed time intervals depending on the current component, and (IV) a predictive assembly duration estimation algorithm.…”
Section: Capability: Dynamic and Adaptive Motionsmentioning
confidence: 99%